Is it Possible to Estimate the Effect of Risedronat Treatment on Bone Mineral Density in Postmenapausal Osteoporosis by Biochemical Marker? - Original Investigation - Ayhan Karadağ; Kaan Uzunca (Galenos Yayinevi, 2006)
In this study we aimed to evaluate and compare the effects of risedronate on bone mineral density (BMD) and biochemical markers in postmenopausal osteoporosis. One hundred three patients with postmenopausal osteoporosis were included in the study. The patients were divided into two groups as group 1 and group 2. The patients in group I were treated with 5 mg risedronate and 500 mg calcium daily, while group 2 were treated only with 500 mg of calcium. Densitometric measurements of lumbar spine and femur were performed before treatment and at the end of 12 months after treatment. Additionally, BMD measurements of 33 patients in group 1 were repeated at the end of 2nd year. Serum levels of osteocalcin and urine C telopeptyde (CTX) levels were measured before therapy and at the 1st and 3rd months of the therapy period. Significant decreases were observed in urine CTX and serum osteocalcin levels beginning from the 1st month in group 1 (p<0.05). In group 1, BMD of femur neck and lumbar spine regions increased significantly at the 12th month of the study. Femur trochanter BMD was also found to increase when compared with pretreatment values at the end of the second year evaluation (p<0.05). No significant correlation of urine CTX and serum osteocalcin levels which were measured at the 1st and 3rd months of the therapy was found with the densitometric changes at the end of one year in group I (p>0.05). However increase of mean BMD values of femur trochanter at second year according to pre-treatment values correlated with decrease of urine CTX values at the first month (p<0.05). As a result, urine CTX levels measured at the end of the first month of the treatment can help estimate the femur BMD increase in the following years of long term risedronate treatment. (Osteoporoz Dünyasından 2006;12: 74-80)